Reduced Graphene Oxide Conformally Wrapped Silver Nanowire Networks for Flexible Transparent Heating and Electromagnetic Interference Shielding - Yang, Yang; Chen, Sai; Li, Wanli; Li, Peng; Ma, Jiangang; Li, Bingsheng; Zhao, Xiaoning; Ju, Zhongshi; Chang, Huicong; Xiao, Lin; Xu, Haiyang; Liu, Yichun (ACS nano, 2020)
Metal nanowire networks (MNNs) are promising as transparent electrode materials for a diverse range of optoelectronic devices and also work as active materials for electrical heating and electromagnetic interference (EMI) shielding applications. However, the relatively low performance and poor durability of MNNs are limiting the practical application of the resulting devices. Here, we report a controllable approach to enhance the conductivity and the stability of MNNs with their transmittance remaining unchanged, in which reduced graphene oxide conformally wrapped silver nanowire networks (AgNW@rGO networks) are synthesized by selective electrodeposition of GO nanosheets on AgNWs followed by a pulsed laser irradiation treatment. Experimental characterizations and finite-difference time-domain simulations indicate that pulsed laser irradiation at a specific wavelength not only reduces the GO but also welds the AgNWs together through a surface plasmon resonance process. As a result, the AgNW@rGO networks exhibit low sheet resistance of 3.3 Ω/□, average transmittance of 91.1%, and good flexibility. Wrapping with rGO improves the maximum electrical heating temperature of the AgNW network transparent heaters due to the effective suppression of the oxidation and the migration of surface silver atoms. In addition, excellent EMI shielding effectiveness of up to 35.5 dB in the 8.2–12.4 GHz frequency range is obtained as a consequence of the combined effects of dual reflection, conduction loss, and multiple dielectric polarization relaxation processes.